How product attributes influence internationalization: A framework of domain- and culture-specificity - FAN, Terence P. C. (Institutional Knowledge at Singapore Management University, 2015)
This paper introduces two important dimensions of product attributes in the context of internationalization: domain- and culture-specificity. Products can be high or low in domain- or culture-specificity, thereby being one of four broad categories in a two-by-two matrix. This framework of product attributes helps explain a series of gradations on how cultural difference influences the difficulty of selling a product internationally. By examining four cases, one from each of these categories, this paper shows that different product attributes affect the difficulty or ease with which the products of these firms were internationalized. While all four cases were able to derive international sales, the domain- and culture-specificity of their products constrained the international markets these products could feasibly enter into, and how soon this could take place. In general, more culture-specific products face higher hurdles in a culturally dissimilar international market compared with the home market. However, given products of similar culture-specificities, highly domain-specific products tend to have less difficulty in selling to a culturally different international market than products that are not domain-specific.